INVESTASI SWASTA DI INDONESIA - Zuhairan Yunmi Yunan (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2012)
The result of cointegration test shows that the determinant variables in the model with private investment which means, in the long term direction of movement of independent variables with dependent variables. Based on statistical tests, Error Correction Model (ECM) private investment, coefficient of national income variable on short-term is significant and have positive signs. The coefficient of variable error correction term (ECTt-1) are statistically significant at 99% confidence level and has a negative sign. Coefficient ECTt variable is negative means that model in the short term under long-term equilibrium, so that the balance of short-term adjustment process towards long run equilibrium moves upward direction. In the long-term, the economic crisis affects private investment and negative signDOI: 10.15408/sjie.v1i2.2605